Fiber optics flow measuring techniques and feasibility study of its implementation as an angle of attack sensor and stall detector - Ang, Jia Liang (2014)
There is a continuous demand to reduce the cost of energy from wind turbine generators. Active control techniques were found to achieve significant savings in energy production without demanding a huge setup cost. However, a successful active control requires sensing technique that is able to fulfil the key design requirements of a flow sensor to be placed near the blade tip of the wind turbine. The requirements of the velocity sensing design are lightning attraction issues and dust, high reliability, control accuracy and low cost - which the current techniques cannot fulfil. Therefore, with the motivation to drive the improvement of the wind measurement techniques forward, an optical fiber velocimeter was presented as a viable flow measuring device. By integrating the fiber optic flow measurement analytical model and active closed-loop feedback system, this project seeks to offer a potential viable method of velocity measurement. Initially, proof of concept using optical fibers to measure wind velocity was established on a flat surface and it was verified on an aerofoil design. By varying the optical fiber insertion location on the aerofoil, two different fiber optic flow measuring techniques were created. The two different fiber optic techniques are able to bring promising results that could be applied to the two-dimensional flow field of the aerofoil for wind turbine application. Firstly, the fiber optics stall detector was designed to pitch the blade to the maximum Angle of Attack (AOA) before stall occurs. The second technique described the use of the optical fibers as an AOA sensor that can determine the angle of attack and to correctly pitch the blades to the optimum AOA. If the system permits, combining both the AOA sensor and the stall detector would provide a very robust system. The results have shown that the AOA sensor was able to differentiate the AOA intervals and the stall detector was able to capture an increase in fluctuation during the stalling of the blade. With the support of these promising results, both application techniques have demonstrated their capabilities as sensors on an actual wind turbine. This report concludes that the fiber optics are prospective wind sensing techniques in the future but the technology requires further developments as suggested in the report’s future work.